(3GdaQGFO GdOQGQi aj JQLeI GdEeGe GdHNGQis - (3GdYLdhfj , ESeGYjd Hf eMeO Hf YHO GdgGOj GdLQGMj GdOeTbj, CHh GdaOGA,J (B1162 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYGde HLejY GdCTjGA LedI hJaUjdkG s
(3BNQgG (B:s
(3aGddg SHMGfg hJYGdi jefMfG hEjGg GdCLQ GdLRjd s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B325 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B292s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B227 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs